Exploring the practical theological study of congregations - W. J. Schoeman (Acta Theologica)
The first congregation was formed in Jerusalem, giving rise to faith communities throughout the New Testament. In the ensuing two millennia, congregations are found worldwide. The aim of this article is to describe congregations and the study of congregations from a practical theological perspective. An introduction to the study field of congregations is followed by a description of the development of the study field of congregational studies from the perspective of four countries, namely the United States, the United Kingdom, The Netherlands, and South Africa. The aim is not to give a comprehensive historical overview of the discipline, but to trace some trends that have an influence on the discipline within the South African context. The second part of the article describes the exploration of congregations from a practical theological ecclesiology (the identity, mission and ministry of the congregation) and an analytical perspective (external interaction between congregation and community, and the internal life of the congregation). A practical theological ecclesiology and an analytical framework should interact critically with each other.